The Population and Isolates of Potential ACC Deaminase-Producing Rhizobacteria from Rhizospheric Soil of Peanut under Different Moisture Level - Dori Kusuma Jaya; Lolita Endang Susilowati; Zaenal Arifin; Age Iwandaka; Eli Martini (Postgraduate, University of Mataram, 2024)
ACC deaminase-producing rhizobacteria play an important role in enhancing plant growth and health, particularly under environmental stress condition. This study focused on isolating and determining the population of potential ACC deaminase-producing rhizobacteria from the rhizosphere of peanut plants (Arachis hypogea L.) grown under varying moisture level. Bacterial population was measured using the Standard Plate Count (SPC) method on Dworkin-Foster (DF) medium supplemented with 3 mM.L-1 ACC as the sole nitrogen source. The isolated bacteria were screened based on their ability to grow after 24 hours of incubation on the selective medium. Result showed that bacterial colonies on nutrient agar (NA) medium varied in color, while colonies on the selective medium were uniformly white. The total population of ACC deaminase-producing rhizobacteria generally declined as soil moisture decreased, nevertheless, the sample at 80% available water contained fewer bacteria (7.3 x 103 cfu.g-1 soil) than those (9.7 x 105 cfu.g-1) at 50%. In an additional experiment, 9 out of 11 selected isolates were found to potentially produce ACC deaminase, with 5 of these being diazotrophic bacteria. This study contributes valuable information for designing irrigation systems in sustainable land management, particularly concerning plant-beneficial microbes that produce ACC deaminase and help plants tolerate environmental stressors.